Pengaruh Tarif Cukai Rokok dan Profitabilitas Terhadap Debt To Equity Ratio (DER) Perusahaan Rokok yang Terdaftar di BEI Tahun 2017–2024 - Pornama, Dewi Wandani; Hartono, Hartono; Verlandes, Yuliasnita (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
The cigarette industry is a manufacturing subsector that contributes substantially to state revenue through tobacco excise. Rising excise tariffs and firm profitability are presumed to shape corporate financing decisions, as reflected in the Debt to Equity Ratio (DER). This study examines the effect of cigarette excise tariffs and profitability on the DER of cigarette companies listed on the Indonesia Stock Exchange (IDX) during 2017–2024. A quantitative causal design was employed using secondary data drawn from companies’ annual financial statements and official publications of the Directorate General of Customs and Excise. The population comprised all IDX-listed cigarette subsector firms; a saturated (census) sampling technique yielded three companies and 24 firm-year observations. Data were analyzed through multiple linear regression using SPSS. The results show that the cigarette excise tariff has no significant effect on DER, profitability has a significant negative effect on DER, and the two variables jointly do not significantly affect DER. These findings suggest that capital-structure decisions in the cigarette industry are driven more by internal profitability considerations than by external fiscal pressure.